2017
DOI: 10.4995/wrs.2017.4485
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation and expression of follicle-stimulating hormone receptor in young rabbit females

Abstract: <p>To optimise the use of juvenile in vitro embryo transfer technologies in young rabbit females, superovulation was performed in New Zealand White young rabbit females at different ages and the expression mode of follicle-stimulating hormone receptor (FSHR) was explored using real-time quantitative polymerase chain reaction, and in vitro maturation (IVM) together with fertilisation (IVF) was conducted immediately after superovulation. The results showed that (1) the age factor significantly affected sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Animals in this study are of the same age and in principle age is not therefore a factor of variation in hormonal level in this case. Considering other studies, such as that carried out by Zhang et al [53] in New Zeeland female rabbits and Labib et al [54], age and corpus luteum formation can be a factor of hormonal expression.…”
Section: Discussionmentioning
confidence: 99%
“…Animals in this study are of the same age and in principle age is not therefore a factor of variation in hormonal level in this case. Considering other studies, such as that carried out by Zhang et al [53] in New Zeeland female rabbits and Labib et al [54], age and corpus luteum formation can be a factor of hormonal expression.…”
Section: Discussionmentioning
confidence: 99%
“…The culture medium for IVM is considered a key element in the success rate of this technique. In the present study, Ham's F10 medium was used for the first time in rabbit oocyte culture; other studies have used TCM‐199 (Arias‐Álvarez et al., 2018; Zhang et al., 2017). Ham's F10 medium is not as rich and nutritious as the TCM‐199 culture medium.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequent studies have shown successful ovulation by intravenous administration of HCG and intramuscular administration of GnRH (Molina et al., 1987). In most studies on IVM of rabbit oocytes, superovulation has been performed (Viudes‐de‐Castro et al., 2017) by injection of hormonal drugs such as HCG (Izumi et al., 2013), FSH (Zhang et al., 2017), and PMSG (Izumi et al., 2013) to recover the COCs. Unfortunately, superovulation in humans has many serious side effects, such as ovarian hyperstimulation syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations